Limitations and Possibilities for School Enhancement in a Chilean Patagonia Context: Coyhaique Community schools in the Aysén Region, Chile - Retamal Cisterna, Silvia Natalia (2020)
This article shows the limitations and possibilities involved in enhancing schools in the municipality of the Coyhaique commune in Chile´s Patagonia Region according to theoretical constructs on school enhancement and the experience of teachers/principles working in the Coyaique commune. A qualitative study was conducted on transformation processes at schools in the aforementioned area for educational improvement purposes, specifically consisting of a teacher training and school principal skills intervention program[1] (AECID Coyhaique Project). The objective of this study is to look at the institutional and contextual conditioning factors at schools that principals and teachers consider to be important for educational transformation. Data is based on interviews with principals/teachers of nine municipal schools in Coyhaique which were conducted using a socio-anthropological focus. The data reveals a chasm between local understanding of school improvements and theoretical explanations regarding educational transformation. The study concludes that there are factors favoring transformation processes at schools that are also common to schools in Patagonia, such as: redirect the focus on teaching processes and results, provide opportunities for shared discussion, rethink school as a place to organize and train teachers and make schools more accessible to outsiders. However, results vary , to that extent, that they interact with other contextual variables, such as geographic location, sociocultural conditions and inflexibility of Chilean educational policies.    [1] En el marco de un proyecto de apoyo y fortalecimiento educacional en gestión directiva y competencias profesionales docentes, dirigido por Joaquín Gairín (Grupo EDO: http://edo.uab.es) y subvencionado por la Agencia Española de Cooperación Internacional para el Desarrollo (AECID) en la convocatoria de 2007. Ver resultados en Gairín y Castro (2010) y Gairín y Sánchez (2011).